Let's Talk: How Communication Affects Contract Design. Issue 4 (24th November 2015) - Brandts, Jordi; Ellman, Matthew; Charness, Gary
Abstract: We study experimentally how communication changes the effectiveness of contract types when sellers choose unenforceable quality after a possible cost shock. Communication potentially removes conflicting perceptions that may otherwise plague flexible contracts. Indeed, we find that introducing free-form communication sharply reverses an advantage of rigid contracts in favor of flexible contracts, which then deliver much higher earnings. Control treatments that avoid selection effects reveal a strong parallel shift from rigid to flexible. Chat content analysis identifies clarification of post-shock transfers, promises, and personal rapport as key correlates of high earnings, with clarification working only in conjunction with flexible contracts. A communication channel restricted to clarifying transfer plans also favors use of flexible contracts, but mildly compared to chat.